Norwegian scabies in a 4-month-old child after topical corticosteroid therapy. - Jaatar, K.; Aboudourib, M.; Bendaoud, L.; Amal, S.; Hocar, O. (European Journal of Pediatric Dermatology, 2025)
Scabies remains a significant global health issue, affecting over 300 million individuals annually, with the highest incidence observed in children under two years of age. This report presents a case of a 4-month-old boy initially misdiagnosed with atopic dermatitis, for which he received topical corticosteroids. The corticosteroid treatment led to the progression of his condition into crusted scabies, characterized by a hyperinfestation of Sarcoptes scabiei mites. Upon admission to our dermatology department, the child exhibited widespread erythematous papules and crusted lesions, alongside family members who reported intense pruritus and similar lesions. Microscopic examination confirmed the presence of numerous mites and eggs. After ceasing corticosteroid use, the child was treated with Benzyl Benzoate, with significant improvement noted at the 3-week follow-up. This case highlights the potential for misdiagnosis and inappropriate corticosteroid use in infants, leading to local immunosuppression and exacerbation of scabies. The findings underscore the necessity for awareness and proper diagnostic measures to prevent similar occurrences, particularly in young children.